Diagram of Bendix Mass Spectrometer - Bendix Corporation (1970)
Schematic diagram of a section of a Bendix Time-of-Flight Mass Spectrometer, with view of the shock tube, oscilloscope, and attachment for a Knudsen cell or direct inlet system. The diagram is captioned "versatility," presumably to emphasize the adaptability of the Bendix system. The Time-of-Flight Mass Spectrometer (TOFMS) was the flagship analytical instrument of the Bendix Corporation.
Keywords: Oscilloscopes; Scientific apparatus and instruments; Mass spectrometers; Mass spectrometry; Time-of-flight mass spectrometry; Bendix Corporation; Spectrometer industry